The Role of Sensory Research in Planning a Marketing Strategy - Paweł TUREK (Communications of International Proceedings, 2021)
Sensory analysis can play an important role in marketing research and the knowledge of the general practices and standards governing sensory determinations can facilitate the assessment of the effectiveness of applied marketing strategies. The aim of the study was to present the possible ways of using sensory/consumer research in brand strength analysis. The comparison of the results of product tests in which the company logo was either revealed or hidden can provide valuable information regarding the brand strength. As the research shows, the importance of brand loyalty as a predictor of consumer behavior is rather high. Consumers tend to associate given brands with expected level of quality and then are ready to assess a branded product much better than when they are shown the very same product without the indication of the brand. Thus, it seems that building a positive brand image should be one of the main strategic goals for enterprises, as it has a direct impact on the product assessment among consumers. Sensory research may therefore constitute a crucial decision-making link when elaborating marketing strategies and plans and it can also serve to measure the effectiveness of marketing efforts, especially in terms of brand management and in shaping a positive image of the company.
Keywords: Marketing Strategy; Strategic Planning; Consumer; Quality; Brand; Sensory Research